Management of Slums in the Kotaku Program with Sustainable Urban Governance in Batam City - Murtiono, Hendro; Gunawan, IGN Anom; Rinoa, Livvy (ASTONJADRO, 2024)
The impact of urbanization is closely related to urban settlement problems. One of the government’s efforts to solve the problem of housing needs for low-income people in densely populated urban areas is to build vertical housing or flats. The City Without Slums Program (KOTAKU) is one of the strategic efforts of the Directorate General of Cipta Karya, Ministry of Public Works and Public Housing (PUPR) to accelerate the handling of slums in urban areas and support the "100-0-100 Movement", namely 100 percent access to proper drinking water, 0 percent slums, and 100 percent access to proper sanitation. One of the efforts made by the Indonesian government in dealing with slum settlements is the implementation of the Cities Without Slums (KOTAKU) program. This study uses a qualitative research method that aims to understand the phenomenon of what is experienced by research subjects holistically. The results of the study show that from an economic perspective, the KOTAKU program is very well received by the community in the kelurahan environment, because the program includes a capital budget program for the surrounding community. Then in terms of environmental aspects, the KOTAKU program is here to provide solutions for the environment with road repair and drainage cleaning programs. Finally, from the social aspect, the KOTAKU program also has a positive impact on social relations in the urban village environment.